2021
DOI: 10.1136/bmjopen-2020-041708
|View full text |Cite
|
Sign up to set email alerts
|

Turning the tide: a quasi-experimental study on a coaching intervention to reduce burn-out symptoms and foster personal resources among medical residents and specialists in the Netherlands

Abstract: ObjectivesPhysician burn-out is increasing, starting already among residents. The consequences of burn-out are not limited to physicians’ well-being, they also pose a threat to patient care and safety. This study investigated the effectiveness of a professional coaching intervention to reduce burn-out symptoms and foster personal resources in residents and specialists.DesignIn a controlled field experiment, medical residents and specialists received six coaching sessions, while a control group did not undergo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 51 publications
2
34
1
Order By: Relevance
“…Our findings are consistent with prior coaching studies that showed a positive effect in some but not all aspects of physician well-being 17 , 21 , 22 , 23 , 24 , 37 , 38 and that support the theory that more than 1 intervention may be necessary to target multiple facets of well-being. A randomized clinical trial of 6 telephone coaching sessions for primary care physicians decreased burnout and increased job satisfaction but did not reduce stress or turnover intention or increase job efficacy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings are consistent with prior coaching studies that showed a positive effect in some but not all aspects of physician well-being 17 , 21 , 22 , 23 , 24 , 37 , 38 and that support the theory that more than 1 intervention may be necessary to target multiple facets of well-being. A randomized clinical trial of 6 telephone coaching sessions for primary care physicians decreased burnout and increased job satisfaction but did not reduce stress or turnover intention or increase job efficacy.…”
Section: Discussionsupporting
confidence: 91%
“… 38 In a study of medical residents in the Netherlands, 6 face-to-face coaching sessions over 10 months resulted in improved personal resources and reduced burnout symptoms, yet no changes were observed in work engagement or psychological flexibility. 24 Although previous studies show that group coaching supports physicians’ professional identity formation and healthy work-life integration, 39 , 40 these studies did not find an association between group coaching and personal well-being factors, including burnout. The group coaching in these studies had prescriptive content with preselected topics (eg, conflict management) 40 and a different delivery format (ie, 3 full-day sessions and 5 two-hour sessions over 4 months).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…For instance, it may be important to continue coaching even after employees have returned to work. To strengthen work-related self-efficacy, by practicing effective coping skills in the workplace, may benefit sustainable RTW in the long term [ 18 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al 17 provided qualitative analysis of a pilot program showing improved well-being following coaching in a GME setting. Similarly, Solms et al 18 provided evidence of reduced burnout for use with resident physicians in a non-randomized control study. There is also supportive evidence for implementation of coaching methodologies for use by faculty advisors and mentors to improve resident well-being in their respective GME programs.…”
Section: Coaching To Promote Physician Resiliencementioning
confidence: 96%